Doctor's Legal Relationship with Patients and Pharmacy - Subagyo Sri Utomo; Wiwin Triyunarti (Budapest International Research and Critics University, 2022)
The medical profession is a profession accompanied by high morality, where every doctor must be ready at any time to provide assistance to anyone, anytime and anywhere in accordance with professional standards. Public unrest is directed at the medical profession who provides drugs that exceed the quality that should be given to patients or only gives certain drugs directly to patients, so the patient must buy the drug in question at the pharmacy. Of course, there is an interest behind the doctor's habit, namely getting a commission from a pharmaceutical company. This habit is carried out continuously, and the number of doctors involved in the conspiracy is also increasing, even though the doctor is aware that his actions have violated the positive law and harmed his patients. Normative juridical research method, with descriptive analytical specifications. Normative legal research is research that only uses secondary data sources, namely legislation and legal theories. Health issues are no longer only between doctors and their patients, but also involve health workers, financing and so on, including pharmacy. An agreement between a doctor and a patient can be classified as an agreement to do or do something. The agreement occurs when the patient calls the doctor or goes to the doctor, and the doctor fulfills the patient's request to treat him. When doctors perform health services when prescribing to patients, it is a breach of ethics committed by doctors and dentists. Meanwhile, patients who are consumers, wherever they are, all have basic social rights. In one therapeutic class there are many drugs that have the same indication/efficacy under various brand names and generic names produced by various pharmaceutical companies. Of course, the patient hopes that the selection of drugs made by the doctor is the best for the patient's health and is affordable by his financial capabilities. the high number of competitions in the promotion of its drugs so that each company approaches doctors with compensation in the form of rewards.